2010
DOI: 10.1378/chest.09-0982
|View full text |Cite
|
Sign up to set email alerts
|

The Master Settlement Agreement and Its Impact on Tobacco Use 10 Years Later

Abstract: Commentary It has been nearly 10 years since the state attorneys general banded together in a concerted legal effort to recover the costs of caring for smokers who had developed cigarette-related illnesses. To avoid possible bankruptcy, tobacco industry companies agreed to a legal settlement known as the Master Settlement Agreement (MSA). With the MSA, states obtained a 25-year payout of hundreds of billions of dollars from "Big Tobacco." In addition, the tobacco industry was forced to make other concessions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
0
41
1
Order By: Relevance
“…While we cannot directly predict the effects of a television e-cigarette advertising ban, studies of combustible tobacco indicate that such bans are associated with reduced use of the products 16. Lessons learned from the Master Settlement Agreement suggest that e-cigarette manufacturers may simply circumvent a ban on televised ads by increasingly promoting their products through event sponsorship, social media and product websites 17. A recent congressional investigation demonstrated that such e-cigarette promotions already are being used to target US youth 18.…”
Section: Conclusion and Discussionmentioning
confidence: 90%
“…While we cannot directly predict the effects of a television e-cigarette advertising ban, studies of combustible tobacco indicate that such bans are associated with reduced use of the products 16. Lessons learned from the Master Settlement Agreement suggest that e-cigarette manufacturers may simply circumvent a ban on televised ads by increasingly promoting their products through event sponsorship, social media and product websites 17. A recent congressional investigation demonstrated that such e-cigarette promotions already are being used to target US youth 18.…”
Section: Conclusion and Discussionmentioning
confidence: 90%
“…There have been a variety of pharmacologic, public health, policy, legislative, and legal strategies employed to decrease tobacco use and exposure [813]. However, large differences exist in tobacco use by education status, race, and ethnicity, [12] which may contribute to sex and ethnic specific differences in cancer incidence and mortality [14].…”
Section: Introductionmentioning
confidence: 99%
“…COPD often occurs with other comorbidities, and presentation with COPD is a major risk factor for the development of lung cancer (73,106). The fact that tobacco exposure is a key factor in the development of both of these diseases was first denied by the tobacco industry and later accepted, following the Tobacco Master Settlement Agreement in 1998 (52,79).…”
mentioning
confidence: 99%